Optimalisasi Pembinaan Kepala Sekolah Dalam Meningkatkan Kompetensi Guru di SMK Citeureup - Sopian Mansur; Imam Tholkhah; Mohamad Jaenudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
The purpose of this study is to find a portrait of optimizing the development of principals, including: Teacher competence; Teacher discipline; and Responsibility of teachers at Vocational High School PGRI Citeureup Bogor. Next is to find out the form of strategy undertaken by the principal in improving teacher competence. This research uses a qualitative descriptive approach through interviews, observation and documentation. The subjects of this study were the principal, teachers and all staff at SMK PGRI Citeureup Bogor. To reflect the results of the study found: a portrait of optimizing the development of school principals in improving teacher competence is very harmonious. All teachers greatly increase competence when seen in implementing the rules, discipline, and responsibility towards their profession as a teacher. As for the form of the principal's strategy in increasing teacher competency in SMK PGRI Citeureup using formal and informal strategies, namely: involving teachers in seminars, training, conducting supervision, promoting discipline and motivating teachers from the principal to motivate teachers to improve improvements in educational innovation as tangible form of developing teacher competence. It is expected that principals can provide encouragement and coaching in teacher performance regarding competence, discipline and teacher responsibility in an effective and efficient manner so as to improve performance both professionally or by teacher competence in schools.